EFFECT OF HORMONAL AND HERBAL THERAPIES ON TOTAL CHOLESTEROL AND TRIGLYCERIDES PROFILE IN HOLSTEIN FRIESIAN COWS - PATEL, B B; PATEL, D M; PATEL, J A; PATEL, J A; BELSARE, V P (The Indian Journal of Animal Reproduction, 2023)
Twenty-eight recently calved HF cows of University farm were monitored through clinical diagnosisand fortnightly plasma profile of total cholesterol and triglycerides from the day of calving till 75 daypostpartum. The animals were equally divided into four groups, each of seven animals. Group I servedas Control; Group II herbal ecbolic (Van tab), 3 intra-uterine infusions given at weekly interval postpartum;Group Ill received Oxytocin 50 iu and PGF 20 25 mg and Group IV PG F 20 25 mg alone i/m immediatelyafter parturition. The average levels of plasma cholesterol and triglycerides in postpartum cows were106.92 ± 2.53 (range 63.20 to 158.02) mg/di and 12.76 ± 0.14 (range 8.3 to 17) mg/di, respectively.The average fortnightly values from parturition (0 hr) to 75 day postpartum were 69.83± 1.19, 95.64 ±5.45, 121.85 ± 4.38, 134.98 ± 5.80, 148.06 ± 5.17, and 139.44 ± 4.62 mg/di, respectively. Thecorresponding values for triglycerides were 15.20 ± 0.40, 11. 78 ± 0.31, 11.88 ± 0.29, 12.07 ± 0.30,12.41 ± 0 .28, and 11.80 ± 0.24 mg/di, respectively. The pooled means of both total cholesterol andtriglycerides were significantly lower in group-Ill as compared to others. The plasma cholesterol contenton the day of parturition (0 day) was lower in all the groups and then showed a gradual and significantlyincreasing trend till day 75 postpartum, while triglyceride showed reverse trend.
Keywords: Holstein Friesian cows; Hormone therapy; Cholesterol; Triglyceride; Postpartum period